Intelligent Immersion: The current landscape of AI tools in the Mixed Reality development pipeline for creative experiences - Mariza Dima; Damon Daylamani-Zad (Revista de la Asociación Española de Investigación de la Comunicación)
Among the technologies that hold immense potential to revolutionize how we interact with information and digital content, Mixed Reality (MR) offers unique immersive experiences that seamlessly integrate virtual objects into the user's physical environment. This groundbreaking fusion of the physical and digital worlds has a complex development process which is a fertile ground for applications of Artificial Intelligence (AI). This article aims to provide a comprehensive overview of AI tools and their applications, in all stages of the development of MR experiences for the creative sector. It also discusses the challenges and opportunities of incorporating them in the development pipeline and offer some use guidelines as a compass to navigate this rapidly changing landscape.